The effect of preferential voting on the election of women to the Peruvian Congress 2020-2021 - Valles Vasquez, Brissa Elizabeth (Revista Elecciones, 2025)
This study presents a comparative analysis of the actual results—with preferential voting—, and the counterfactual results—without preferential voting—of the 2020 Peruvian congressional elections. The findings show that, contrary to the trend in previous elections, preferential voting had a positive effect on women’s representation. To explain these results, I analyzed different elements of the Peruvian electoral system to determine which factors allowed the preferential voting to favor a greater number of female candidates in 2020. This article concludes that the non-simultaneity of presidential and congressional elections, so as party magnitude, and the position of women on party lists are the main elements which, in conjunction with the preferential voting, benefited a larger number of female candidates in 2020.